The Fulfillment of Women's and Children's Rights Post-Divorce in Judicial Decisions of the Unaaha Religious Court - Suriani, Suriani; Aini, Nurul; Marlin, Marlin; Fitriadi, Muh.; Darwis, Rizal; Baharuddin, A. Zamakhsyari (Jurnal Ilmiah Al-Syir'ah, 2024)
The purpose of this study is to describe and analyze the decisions of the Unaaha Religious Court in guaranteeing the rights of children and women after divorce and to examine the constraints of the panel of judges of the Unaaha Religious Court in guaranteeing the rights of women and children in case decisions. This research is a normative-empirical research. Data collection techniques and legal materials are document studies and interviews. While the process of data analysis is carried out in three steps, namely: first, identification of legal facts. secondly, examining or and seeking legal norms related to legal facts. Third, applying legal norms to legal facts. The results of this study show that: First, in the period from July 2021 to June 2022 the Unaaha Religious Court decided 493 divorce and divorce cases. Of the 493 cases that have been decided, only 22 cases involving the fulfillment of the rights of wives or children. Where the reasons for fulfilling these rights can be made into four (4) typologies. First, because it was requested in the convention as many as 12 cases. Second, because of an agreement in mediation in 8 cases. Third, because the posita of the application is 1 case. Fourth, because of the posita lawsuit of 1 case. From the four typologies it can be concluded that the judges have not exercised their rights ex-officio in order to fulfill the rights of women and children. Therefore, it can also be concluded that the judges have not fully implemented the Letter of the Director General of Badilag Number 1669/DJA/HK.00/5/2021 Concerning Guarantees for the Rights of Post-Divorce Women and Children. Second, the constraints faced by judges in fulfilling the rights of women and children in case decisions, namely: 1) the financial ability of the husband or father, 2) the ability of the parties in the evidentiary process, 3) the presence of the parties (wife or husband) in the trial , 4) there is no coordination and cooperation between the Religious Courts and related agencies in the case of parties who work as ASN/PNS.